Industry 4.0: proposing a framework - Silva, Carlos Eduardo; Cardoso, Rodolfo; Baptista Narcizo, Ramon; Maciel Gonçalves, Luiza; Carvalho, Yohana (Archives of Business Research, 2020)
The term Industry 4.0 has gained prominence in academic and business discourses in recent years, having its concept related to the so-called fourth industrial revolution. Goal: The present research aims to develop and present a framework with the concepts of Industry 4.0. Methodology: The study started from a quantitative analysis of the academic articles available in the Scopus database. Subsequently, a qualitative analysis of articles and technical reports (mostly) was carried out to obtain a more applied technological vision in the industry. With this, technological clusters were built and, finally, the Industry 4.0 framework was proposed. Results: As a result, it was possible to establish an overview of the publications, highlighting the main conceptual views of the different terms that converge for the fourth industrial revolution, as well as the main technologies associated with Industry 4.0, systematizing the knowledge in the industry 4.0 framework. Limitations of the investigation: The search has been limited to available and selected papers for reading. Practical implications: The practical contribution has been satisfactorily evaluated to assist future research on the subject. Value: Finally, the main contribution of the work is the creation of a framework that synthesizes and systematizes the relationships among the main characteristics, technologies, products and business models of the 4.0.